2009
DOI: 10.1063/1.3276551
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance-based study of ordered layering on the surface of alumina nanoparticles in water

Abstract: Layering of water molecules on the surface of alumina nanoparticles in an alumina/water nanofluid is studied using nuclear magnetic resonance ͑NMR͒. The data suggest that a thin ordered layer ͑ϳ1.4 nm͒ of water molecules surrounds each nanoparticle. This ordered layer increases the nanoparticle effective volumetric fraction; however, the nanofluid thermal conductivity appears to be unaffected by this layer, and in good agreement with Maxwell's effective medium theory. Furthermore, the NMR data suggest that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(34 citation statements)
references
References 26 publications
(28 reference statements)
0
34
0
Order By: Relevance
“…[12][13][14][15][16][17] Mass transfer in nanofluids was extensively reviewed in a recent published article. 18 In the field of mass transfer in nanofluids, there are a few researches dealt with mass diffusion in nanofluids 10,12,[19][20][21][22][23][24][25] and more researches investigated the influence of nanoparticles on convective mass transfer. 13,15,16,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Nevertheless, most researches on convective mass transfer in nanofluids are related to the gas absorption processes [26][27][28][29][30][31][32][33][34][35] and there have been limited attempts to use nano...…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Mass transfer in nanofluids was extensively reviewed in a recent published article. 18 In the field of mass transfer in nanofluids, there are a few researches dealt with mass diffusion in nanofluids 10,12,[19][20][21][22][23][24][25] and more researches investigated the influence of nanoparticles on convective mass transfer. 13,15,16,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Nevertheless, most researches on convective mass transfer in nanofluids are related to the gas absorption processes [26][27][28][29][30][31][32][33][34][35] and there have been limited attempts to use nano...…”
Section: Introductionmentioning
confidence: 99%
“…Veilleux and Coulombe [24] measured the tracer mass diffusion of Rhodamine 6G in alumina nanofluids and observed that dye diffusion coefficient at an optimum nanoparticles concentration was ten times larger than that in the de-ionized water [24]. By using the pulsed field gradient nuclear magnetic resonance method, Turanov and Tolmachev [25] and Gerardi et al [26] measured the selfdiffusion coefficient of water in the aqueous suspension of SiO 2 and Al 2 O 3 nanoparticles, respectively. They showed that nanoparticles decreased mass diffusion coefficients by about 30 and 10 %, respectively [25,26].…”
Section: List Of Symbolsmentioning
confidence: 97%
“…Mass transfer studies in dye-diffusion by Krishnamurthy et al 1 and others [2,3] have demonstrated, through dramatic visual effects, that the presence of nanoparticles increases the effective diffusivity up to 14 folds. Yet, when carried out in other system configurations, there are some cases where no enhancement [16,17] and even a lowering of the diffusivity [18][19][20] are observed. Various possibilities have been advanced in an attempt to explain these intriguing observations: Brownian motion, micro-convection [1,2], interfacial complexation [16], dispersion model [21], etc., but none of them have been backed with conclusive evidence.…”
Section: Introductionmentioning
confidence: 99%
“…For a homogeneously mixed system, where the nanoparticles and the solute are uniformly dispersed, and the diffusivity is measured using Fluorescence Correlation Spectroscopy (FCS) [17] or Nuclear magnetic resonance (NMR) [18,19], no enhancement or a small lowering of the diffusivity of the solute has been reported. A significant * p.sunthar@iitb.ac.in enhancement is observed only in an inhomogeneous system (various configurations are shown in Figure 1) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%